Driving development: Japanese automotive investment and industrial transformation in Indonesia's New Order era, 1967-1998 - Wardoyo, Stedi (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2025)
This study examines the historical development and implications of Japanese Indonesian cooperation in the automotive sector. While bilateral relations between these nations encompass multiple industries, the automotive sector, particularly passenger vehicles, represents a critical engagement area. The research employs a qualitative, descriptive methodology to analyze this economic relationship. Despite Indonesia's diverse industrial landscape—spanning manufacturing, fisheries, maritime resources, forestry, automotive production, and mining—the automotive sector has emerged as one of the country's top ten export commodities. Japan, a global leader in automotive manufacturing, has actively pursued bilateral cooperation in this sector. However, Indonesia's challenges in meeting established targets have hindered the full realization of planned initiatives. The study reveals an asymmetric relationship characterized by Indonesia's growing dependence on Japan's automotive industry. This dependency is evidenced by several key indicators: escalating imports from Japan, relatively low Indonesian export values, substantial Japanese investment flows, and the dominant market presence of Japanese manufacturers like Toyota and Nissan. As a result, Indonesia has primarily evolved into a significant consumer market for Japanese automotive products rather than developing as an independent manufacturer. Critically, this study finds how bilateral cooperation between Japan and Indonesia, while offering certain benefits, has simultaneously strengthened patterns of economic dependency in the Indonesian automotive sector.